ANALISA PERHITUNGAN, PENYETORAN, DAN PELAPORAN PPH 21 ATAS PEMOTONGAN PPH 21 PADA PT. YELLOWFIT GROUP INDONESIA - Nanan Karyadi; Maulana Prawira Yoga; Fatin Rahimatun Rashidah (REMITTANCE: JURNAL AKUNTANSI KEUANGAN DAN PERBANKAN, 2021)
Taxes are a very important source of state revenue in the development of the country. The size of the tax will determine the capacity of the state budget to finance state expenditures, both for development financing and for routine budget financing. Companies as corporate taxpayers or company owners must withhold income tax article 21 on the employment relationship between employees and the company. If the company does not carry out the tax withholding obligation, it will be subject to applicable tax sanctions and the authority given to the company only withholds taxes owed to employees, not withdrawing or receiving taxes. PT. Yellowfit Group Indonesia is correct in carrying out the mechanism for depositing and reporting Income Tax Article 21 following tax regulations, which is preceded by depositing an SSP or e-billing which is deposited through Mandiri i-banking before the 10th of the following month, followed by reporting the e-SPT Period before the date of next 20 months